Smudge's grumpy day - Moss, Miriam; Chapman, Lynne 1960-. (London Gullane Children's Books, 2001)
Smudge is so grumpy she runs away from home to her treehouse.
Keywords: Anger -- Fiction; Runaways -- Fiction; Children's stories -- Pictorial works